Sacramental Shopping : Louisa May Alcott, Edith Wharton, and the Spirit of Modern Consumerism - Sherman, Sarah Way (Book collections on Project MUSE., 2013)
This book illuminates consumer culture and its challenges to American identity and values as described in two classic novels.